Gift of Vision - Doorstep-to-Doorstep Outreach Eye Care Model, Sankara Model of Accessible and Affordable Eye Care, and its Impact on the Elderly - Kaushik Murali; Bharath Balasubramanian; RV Ramani; Vidhya Chandran; Malavika Mani (Wolters Kluwer Medknow Publications, 2024)
Vision loss among the elderly is a major health-care problem. Vision impairment is associated with a decreased ability to perform activities of daily living and an increased risk for depression. Cataract is a common cause of vision impairment among the elderly, but surgery is often effective in restoring vision. We describe the Sankara model of Gift of Vision, the doorstep-to-doorstep model of community eye care that offers high quantity-high-quality eye care. Our model demonstrates how a cost-effective one-time intervention such as a cataract surgery not only restores vision but also their quality of life.